(3GdTjRhaQjfjGs (3PgGf aUGe GdTNUjI h YdGLgs (3OQGSI ai GdUMI GdfaSjI (B= Schizophrenias causes and treatment - (3GdYjShj , YHO GdQMef eMeOs ((3GdCScfQjI, eUQs (3efTCI GdeYGQas, 2007)
(3jSJYQV gPG GdcJGH GdJWhQ GdJGQjNi deaghe aUGe GdTNUjI, HhUag ef GcKQ GdGeQGV GdYbdjI Ch GdPgGfjI NWhQI hGfJTGQG ai GdhbJ GdQGgf(B. (3GdJTNjU GdObjb dPgGf GdaUGe hGge GYQGVg hNGUI GdgPGAGJ Ch GdVdGdGJ hGdgdGhS hGdJHdO GdYGWai hGdhLOGfi(B. (3CfhGY GdaUGe hGdaQb Hjfg hHjf GdYUGH hJYOO GdTNUjI(B. (3GdfXQjGJ GdJi hVYJ dJaSjQ fTCI eQV GdaUGe hCSHGHg GdhQGKjI hGdfaSjI hGdHjhdhLjI(B. (3GSGdjH YdGL eQVi GdaUGe hcjajI GdJYGed GdMSf eYge hWQb GdhbGjI ef GdGUGHg HGdaUGe(B. (3GdYdGL GdfaSi GdJMdjdi hGdYdGL GdSdhci hGdYdGL GdWHi deQVi GdaUGes
Mans
3 6 11
Keywords: (3GdCeQGV GdYbdjIs; (3GdLfhfs; (3GdPgGfs; (3GdTNUjIs -- (3GVWQGHGJs; (3GdUMI GdfaSjIs; (3GdWH GdYbdis -- (3GVWQGHGJs; (3GdWH GdYbdis; (3GdWH GdfaSis; (3GdaUGes -- (3GdLhGfH GdUMjIs; (3GdaUGes -- (3JTNjUs; (3GdaUGes; (3GdaUGes -- (3Yde faSs; (3GdeNs -- (3CeQGVs; (3GdgdhSIs